THE CHANGES IN EATING HABIT AFTER NUTRITIONAL EDUCATION ON ANEMIA MATERNAL - Ramadhan, Riyan Rahmat; Askhori, Samsul; Ismah, Zata; Mariana, . (LIFE: International Journal of Health and Life-Sciences, 2019)
According to WHO (2008), globally the prevalence of anemia in pregnant women worldwide is 41.8%. Anemic pregnant women are wrong factors due to poor diet. Nutrition education is one of the preventive activities in improving the diet of pregnant women. A good diet during pregnancy can help the body overcome special requests for pregnancy, and have a positive influence on the health of the baby. This study aims to determine changes in consumption of eating patterns in anemic pregnant women after being given nutritional education in the city of Palembang. This type of research uses quantitative methods with an experimental desain. The population in this study were pregnant women in Palembang City. The study sample consisted of 41 respondents (18 anemia, 23 normal). The collection technique used random sampling technique. Statistical test results show that there is a significant influence between nutritional education and rice consumption patterns (p-value 0.013), animal protein consumption (p-value 0.015), vegetables (p-value 0.03) in pregnant women.